RELATIVITY RELATIVELY SIMPLE

Lorentz Transformation:

v>0; v<c

X’ = gamma *( X – vT)

T’ = Gamma * (T – (v/c²) *X)

Gamma =1 / sqrt (1-(v/c)²)

X = c * T.

This reduces to :

X’ = gamma  * X * (1-v/c) = X * sqrt((1-v/c) / (1+v/c))

T’ = gamma * T * (1 – v/c) = T * sqrt((1-v/c) / (1+v/c))

or :

sqrt(1-v/c) * X = sqrt(1+v/c) * X’

and

sqrt(1-v/c) * T  = sqrt(1+v/c) * T’

Note formula is symmetrical for v and -v,

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out /  Change )

Twitter picture

You are commenting using your Twitter account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )

Connecting to %s